1990
DOI: 10.1016/s0022-5193(05)80750-7
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic dynamics in an ionic model of the propagated cardiac action potential

Abstract: We simulate the effect of periodic stimulation on a strand of ventricular muscle by numerically integrating the one-dimensional cable equation using the Beeler-Reuter model to represent the transmembrane currents. As stimulation frequency is increased, the rhythms of synchronization { 1 : 1 -* 2 : 2 -* 2 : 1 -* 4: 2 -* irregular-* 3 : 1 -* 6: 2 -* irregular-* 4: 1 -* 8 : 2 -*... --~ 1 : 0} are successively encountered. We show that this sequence of rhythms can be accounted for by considering the response of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 52 publications
6
72
1
1
Order By: Relevance
“…From this bifurcation diagram it appears that the phase-locking regions are separated by intervals of irregular dynamics. Such a sequence has also observed in numerical simulations of the Beeler-Reuter model (Lewis and Guevara 1990). Fig.…”
Section: = '=supporting
confidence: 68%
See 2 more Smart Citations
“…From this bifurcation diagram it appears that the phase-locking regions are separated by intervals of irregular dynamics. Such a sequence has also observed in numerical simulations of the Beeler-Reuter model (Lewis and Guevara 1990). Fig.…”
Section: = '=supporting
confidence: 68%
“…6. This type of bistability was "rst found in maps by Guevara et al (1984) and later found by Lewis and Guevara (1990). Bistability between two stable solutions with di!erent rotation numbers occurs in many other dynamical systems as well (Aronson et al 1986, Boyland 1986, Rinzel and Troy 1983.…”
Section: Numerical Results On Resonance In Case IIImentioning
confidence: 66%
See 1 more Smart Citation
“…To go beyond the case of a single pulse circulating in a ring, periodically stimulated excitable media have been studied in the context of alternans [41,42,35,34,36,37]. In [41,36] one-dimensional maps were developed to study the Hopf bifurcation and the transition to conduction blocks.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…[1,2,3,4] For the 1-D loop, most work has been done assuming the membrane to be a continuous and uniform cable with constant intracellular axial resistivity. [5,6,7,8,9,10,11,12,13,14,15] For different models representing the ionic properties of the membrane, propagation was found to change from stable period-1 propagation to quasi-periodic reentry when the length of the loop was reduced below a critical length. The quasi-periodic reentry was characterized by a spatial oscillation of the action potential duration as propagation proceeded around the loop.…”
Section: Introductionmentioning
confidence: 99%